2007
DOI: 10.1097/hjr.0b013e3281764429
|View full text |Cite
|
Sign up to set email alerts
|

Trends in cardiovascular risk factor prevalence (1995-2000-2005) in northeastern Spain

Abstract: The cardiovascular risk factor prevalence change in Gerona was marked in this decade by a shift of total cholesterol and low-density lipoprotein cholesterol distributions to the left, independent of the increase in lipid-lowering drug use, and better hypertension control with increased use of antihypertensive drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
93
0
14

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 160 publications
(116 citation statements)
references
References 36 publications
(31 reference statements)
2
93
0
14
Order By: Relevance
“…In our study, patients under VPA therapy were less affected by dyslipidemia than the rest of the population. We would speculate that the variety of lipid profile findings analyzed in the systematic review might correspond to differences not only in the study design (Grau et al., 2007) but also in the geographical region or dietary habits. Concerning new AEDs, we observed that the levetiracetam group had more CRFs, compared to patient groups taking other drugs (in monotherapy).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, patients under VPA therapy were less affected by dyslipidemia than the rest of the population. We would speculate that the variety of lipid profile findings analyzed in the systematic review might correspond to differences not only in the study design (Grau et al., 2007) but also in the geographical region or dietary habits. Concerning new AEDs, we observed that the levetiracetam group had more CRFs, compared to patient groups taking other drugs (in monotherapy).…”
Section: Discussionmentioning
confidence: 99%
“…2,23 This decline is mainly attributed to reductions in the majority of risk factors, such as smoking, hypertension, and hypercholesterolemia, as well as improvements in medical diagnosis and treatment. [24][25][26][27] However, socioeconomic inequalities in IHD mortality persist and are even increasing in many western European countries. 3,[28][29][30][31][32] Among studies analyzing the relationship of IHD mortality with residential area socioeconomic level, those focusing on urban areas are of particular interest, since in these areas, stronger associations have been documented between area socioeconomic level and IHD mortality than in urban peripheral or rural areas.…”
Section: Introductionmentioning
confidence: 99%
“…En otro estudio, en el que también se valoraban los cambios en la prevalencia de diferentes factores de riesgo entre los años 1995-2005, se observó en el año 2005 una prevalencia del 39% 4 , muy similar a la observada en el segundo examen de nuestro estudio. Así pues, parece clara la tendencia en nuestro país al aumento de la prevalencia de HTA tal como observamos en la población general de Albacete.…”
Section: Discusionunclassified
“…Los estudios de tendencias demuestran descensos de la mortalidad por ECV a pesar de existir un incremento en la prevalencia de los denominados factores de riesgo cardiovascular (F CV) modificables (obesidad, hipertensión arterial, diabetes...) [2][3][4][5][6][7] . Esta paradoja puede estar justificada, además de por una mayor supervivencia tras un evento agudo, por una mejora en el grado de conocimiento y control de esos factores de riesgo y por un descenso en la prevalencia y mortalidad atribuible al tabaquismo 6 .…”
Section: Introductionunclassified